Flaming to control weeds in seashore paspalum (Paspalum vaginatum Sw.) turfgrass - Luisa Martelloni; Marco Fontanelli; Lisa Caturegli; Monica Gaetani; Nicola Grossi; Simone Magni; Andrea Peruzzi; Michel Pirchio; Michele Raffaelli; Marco Volterrani; Christian Frasconi (Journal of Agricultural Engineering, 2019)
Weed control is crucial to ensure that turfgrass is established effectively. Although herbicides are commonly used to control weeds in turfgrasses, environmental and public health concerns have led to limiting or banning the use of synthetic herbicides in urban areas. The species seashore paspalum (Paspalum vaginatumSw.) is susceptible to such herbicides. Flame weeding could be an alternative to the use of synthetic herbicides for selective weed control in seashore paspalum. In this study, five different liquefied petroleum gas (LPG) doses of flaming (0, 61, 91, 157 and 237 kg ha-1) were tested in order to find the optimal dose, in terms of weed control and costs. The aim was to maintain a seashore paspalum (cultivar ‘Salam’) turf free of weeds during spring green-up, and at the same time avoid damaging the turfgrass. Using a self-propelled machine designed and built at the University of Pisa, flaming was applied three times when weeds started growing and the turfgrass started green-up. Our results highlight that an LPG dose of 157 kg ha-1was the most economic dose that led to a significant reduction in initial weed cover and density, enabling the turfgrass to recover three weeks after the third application.